High Diversity in CMA(3)/DAPI-Banding Patterns in Heteropterans - Bardella, V. B. [UNESP]; Grazia, J.; Fernandes, J. A. M.; Vanzela, A. L. L. (Karger, 2014)
Heteroptera is the most numerous and diverse suborder of Hemiptera, with about 38,000 species. This diversity also involves cytogenetic features, including chromosome number and a sex determining system. Information about heterochromatin occurrence and distribution is scarce in heteropterans, but still, there is some evidence of variability. We determined the chromosome number and CMA(3)/DAPI-banding pattern of 179 individuals of 25 heteropteran species from Brazil. Eight species of Pentatomidae exhibited a constant chromosome number (2n = 12 + XY), but in Coreidae (12 species), Largidae (1 species), Rhopalidae (1 species), and Pyrrhocoridae (3 species), the numbers ranged from 2n = 10 + 2m + X0 to 2n = 24 + 2m + X0. Although there were no large differences in the chromosome size between species, the CMA(3)/DAPI-banding patterns differed markedly. Among the genera, species of Edessa, Spartocera, Hypselonotus, Phtia, Holhymenia and Euryophthalmus showed a large accumulation of heterochromatin, while the other species exhibited few or no heterochromatic bands. In general, when heterochromatin was more accumulated, this occurred preferentially at terminal positions, except in Holhymenia histrio, which exhibited intercalary bands. This study made it possible to identify some chromosome rearrangements and to enhance our knowledge of the evolutionary mechanisms that determine karyotype differentiation in Heteroptera. (C) 2013 S. Karger AG, Basel
Keywords: CMA(3)/DAPI banding; Chromosome number; Heteroptera; Holokinetic chromosomes; Repetitive DNA